African Canadian Women and the Question of Identity - Wane, Njoki Nathani (Atlantis, 2009)
Canada is a nation that embraces diversity and multiculturalism as its corner stone for building the sense of belonging for all her citizens. Many Black Canadian women, however, feel excluded and not part of the Canadian mosaic. This paper shows the complexities associated with understandings and interpretations of identity and discusses Black women's question of identity as situated in Black Canadian feminist theory.